Adaptation and psychometric evaluation of the Chinese version of the functional assessment of chronic illness therapy spiritual well-being scale among Chinese childhood cancer patients in China - Liu, Qi; Ho, Ka-Yan; Lam, Katherine-Ka-Wai; Lam, Winsome; Cheng, Eileen-Hui-Lin; Ching, Shirley-Siu-Yin; Belay, Getaneh Mulualem; Wong, Frances-Kam-Yuet (Frontiers in Psychology, 2022)
Background: Spiritual well-being is a source of strength for childhood cancer patients, helping them to cope with and adapt to cancer. The availability of a valid and reliable instrument for accurately assessing spiritual well-being is crucial for the development of interventions to improve the spiritual well-being of childhood cancer patients. Methods: A cross-sectional study was conducted among 412 Chinese childhood cancer patients aged 8–17 years. Participants were invited to respond to the Chinese version of the adapted Functional Assessment of Chronic Illness Therapy Spiritual Well-being (FACIT-Sp) Scale, the Center for Epidemiology Studies Depression Scale for Children (CES-DC), and the Pediatric Quality of Life Inventory 3.0 Cancer Module (PedsQL). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to assess the structural validity of the FACIT-Sp. Content validity, convergent validity, internal consistency and test–retest reliability at 2 weeks were also examined. Results: Cronbach’s alpha was 0.815, indicating good internal consistency. The content validity index values for items ranged 0.8 – 1.0 and that for the scale was 0.84, indicating appropriate content validity. There was a positive correlation between FACIT-Sp and CES-DC scores, and a negative correlation between FACIT-Sp and PedsQL scores. The results indicated that the Chinese version of the adapted FACIT-Sp showed reasonable convergent validity. Exploratory factor analysis yielded a four-factor model, which was supported by confirmatory factor analysis. Conclusions: The current findings indicated that the Chinese version of the adapted FACIT-Sp Scale is a reliable and valid instrument for assessing spiritual well-being among Chinese childhood cancer patients. Given the importance of spiritual well-being in the cancer trajectory, this instrument can be applied in clinical settings for routine assessment.